LEGAL POSITION OF THE CAPITAL CITY OF THE ARCHIPELAGO IN THE INDONESIAN CONSTITUTIONAL SYSTEM - Husni Thamrin; Norhayah Zulkifli; Muhammad Husni Fahrudin (Awang Long Law Review, 2026)
This study aims to analyze the legal provisions for the Indonesian Capital City, its legal status within the Indonesian constitutional system, and its legal implications for governance. This study begins with the establishment of the Indonesian Capital City through Law Number 3 of 2022 as amended by Law Number 21 of 2023, which not only relocates the nation's capital but also establishes a special regional government design through the Indonesian Capital City Authority. This study uses normative legal methods with statutory, conceptual, and constitutional approaches. The data used are primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that the legal provisions for the Indonesian Capital City have a constitutional basis based on the principles of the rule of law, regional governance, central-regional relations, and the recognition of special regional government units. Formally, the Indonesian Capital City is positioned as a special regional government unit at the provincial level, but substantively exhibits an administrative-centralistic character because it is led by a Head of Authority appointed by the President, holds a ministerial position, and is not accompanied by a Regional People's Representative Council (DPRD). Therefore, the IKN can be understood as a sui generis constitutional entity. Its legal implications are evident in the narrowing of local political autonomy, the strengthening of vertical central-regional relations, the weakening of local checks and balances, the limitation of community political representation, and the potential for normative disharmony within the Indonesian constitutional system.